Business Ethics Perception as Moderating Variable on the Influence of Management Accounting System to Managerial Performance (Study at PT Bank Mandiri (Persero), Tbk.) - Christina, Veronica; Haizam Mohd Saudi, Mohd; ., Silviana; Nurani, Nina; Sinaga, Obsatar (International Journal of Engineering and Technology, 2018)
This study aims to determine the effect of management accounting systems on managerial performance with business ethics perception as a moderating variable in PT Bank Mandiri (Persero) Tbk. The populations in this study were top, middle and lower managers who were responsible for the performance of ten branch offices of PT Bank Mandiri (Persero) Tbk in the city of Bandung and the population was 80 people. The results showed that business ethics perception was able to moderate the influence of management accounting systems on managerial performance.Â Â